Analysing the Urban Housing Challenge in Harare, Zimbabwe Through the Wicked Policy Problems Framework - Poshai, Leon; Chilunjika, Alouis; Intauno, Kudakwashe (Journal of Government and Civil Society, 2024)
This article analyses how urban housing challenges in Harare, Zimbabwe have transformed into a wicked policy problem and further proposes some measures for managing this problem. The article uses a qualitative research approach in which an explanatory case study research design and key informant interviews are used to investigate how the provision of urban housing facilities has become a demanding task for the City of Harare in Zimbabwe. The study reveals how rapid population growth in Harare has escalated the demand for, and subsequent shortage of housing facilities leading to housing access complexities and persistently depreciating housing conditions in this city. The article argues that housing challenges in Harare are symptoms of other social problems such as unemployment, poverty, social inequalities, misgovernance and institutional corruption. This article proposes context-specific measures for harnessing a holistic approach that can be used for managing urban population explosions and sustainable housing provision in developing countries with Harare in Zimbabwe used as the social laboratory for analysis. This article has a practical and theoretical orientation as it proposes the measures that can be adopted to manage the wicked urban housing policy problem in Zimbabwe.Artikel ini menganalisis bagaimana tantangan perumahan perkotaan di Harare, Zimbabwe telah berubah menjadi masalah kebijakan yang buruk dan selanjutnya mengusulkan beberapa langkah untuk mengatasi masalah ini. Artikel ini menggunakan pendekatan penelitian kualitatif yang menggunakan desain penelitian studi kasus eksplanatori dan wawancara informan kunci untuk menyelidiki bagaimana penyediaan fasilitas perumahan perkotaan telah menjadi tugas berat bagi Kota Harare di Zimbabwe. Studi ini mengungkapkan betapa pesatnya pertumbuhan penduduk di Harare telah meningkatkan permintaan, dan kekurangan fasilitas perumahan yang menyebabkan kompleksitas akses terhadap perumahan dan terus-menerus memperburuk kondisi perumahan di kota ini. Artikel tersebut berpendapat bahwa tantangan perumahan di Harare adalah gejala dari masalah sosial lainnya seperti pengangguran, kemiskinan, kesenjangan sosial, kesalahan dalam pemerintahan dan korupsi institusional. Artikel ini mengusulkan langkah-langkah spesifik konteks untuk memanfaatkan pendekatan holistik yang dapat digunakan untuk mengelola ledakan populasi perkotaan dan penyediaan perumahan berkelanjutan di negara-negara berkembang dengan Harare di Zimbabwe digunakan sebagai laboratorium sosial untuk analisis. Artikel ini memiliki orientasi praktis dan teoretis karena mengusulkan langkah-langkah yang dapat diambil untuk menangani masalah kebijakan perumahan perkotaan yang buruk di Zimbabwe.